TO WHAT EXTENT EFL LEARNERS HAVE MASTERED CONCORD - Isyam, Amri (English Department FBS UNP, 2009)
Concord is one of grammatical items from which many EFL learners still commit deviations. Their deviations from this grammatical item are a reflection of their concord mastery. There are five kinds of concord. However, this article aims at describing to what extent EFL learners have mastered 3 types of concord: subject-verb, subject-complement, and subject-object. The article was based on a part of the research entitled EFL Learnersâ€™ Concord Mastery and their grammatical Deviations carried out by the writer two years ago. The population was 120 EFL learners consisting of three classes of the third year students of the English Department of the Faculty of Languages, Literature, and Arts of the State University of Padang, and with cluster-sampling technique one class of them was chosen as the sample comprising of 32 subjects. The data were gathered through a fifty-item test with one administration, but the sample students were required to write 4 versions of the answers. There were 2 versions of concord mastery (CM), CM1 which was based on the correct answers of version 1 and CM 2 which was based on the correct answers after the grammatical deviations were split into mistakes and errors. With the use of quantitatively descriptive method, it was found out that on the average the EFL learnersâ€™ CM1 was only 64 which was categorized into satisfactory level based on 5 achievement categories proposed by UNP (2005): excellent, good, satisfactory, weak, and poor. However, CM2 on the average increased significantly to 70, and the achievement category changed into good level. The writer believes CM2 was the actual concord mastery of the EFL learners. Thus, he suggests that an EFL lecturer/ teacher not neglect concord and (s)he split grammatical deviations into mistakes and errors in order to know actual mastery of any grammatical item.Â